Development of automatic feeding machine for aquaculture industry - Yeoh, S. J.; Taip, Farah Saleena; Endan, Johari; A. Talib, Rosnita; Mustapa Kamal, Siti Mazlina (Universiti Putra Malaysia Press, 2010)
Aquaculture is a growing industry with a great potential towards the contribution of the country’s total fish requirement. Serious efforts have been done to develop and improve the production of fish by rearing high value fish in tanks or ponds. Under the Third National Agricultural Policy (1998-2010), the target is to annually produce 1.93 million tonnes of fish worth approximately RM8.3 billion by the year 2010. Consequently, the development of an automatic fish feeding machine can be very beneficial to the growth of the aquaculture industry. This device was developed to overcome labour problems in the industry and introduce a semi-automatic process in the aquaculture industry. It has the ability to dispense dried fish food in various forms such as pellets, sticks, tablets or granules into fish tanks or ponds in a controlled manner for a stipulated time. The automatic fish feeder is controlled by a digital timer and it is capable of feeding the fish in accordance with a pre-determined time schedule without the presence of an operator, and at a feeding rate of 250g/min. The feeder can be adjusted to the desired height and conveniently moved around to be positioned adjacent to the pond or tank. Meanwhile, its hopper can be covered and easily dissembled to change the size of the hopper to accommodate different capacities of feed. This automatic fish feeder can be implemented in aquaculture system to convenience to fish culturists.